Stress, resilience, and moral distress among health care providers in oncology during the COVID-19 pandemic - Alrjoub, Waleed; Alarjeh, Ghadeer; Ammar, Khawlah; Shamieh, Abedalrahman; Harding, Richard; Booth, Christopher; Sullivan, Richard; Al-ruzzieh, Majeda; Mansour, Asem; Shamieh, Omar (Frontiers in Public Health, 2023)
Background: The coronavirus pandemic has potential implications for stress levels and resilience among oncology healthcare professionals (HCPs). This study aims to assess perceived stress, resilience, and moral distress levels among oncology HCPs in Jordan during the pandemic and identify associated risk factors.Methods: An online cross-sectional survey was conducted among oncology HCPs in Jordan using three validated tools: Perceived Stress Scale (PSS), Connor-Davidson Resilience Scale (CD-RSIC), and Moral Distress Thermometer (MDT). Seven items were used to assess sources of stress.Results: A total of 965 participants enrolled with a 74% response rate. The participants' ages ranged from 20 to 74 (mean=32.74, SD=5.197), with 79.1% males, 45.1% were physicians, 32.6% were public hospital workers, 57.1% were married, and 56.6% had children below 18 years. Findings indicated moderate perceived stress (Mean=15.87, SD=5.861), low resilience (Mean=29.18, SD=5.197), and high moral distress (Mean=4.72, SD=2.564). Females, unmarried individuals, and younger age groups exhibited higher PSS (P=0.009, P<0.001, and P˂0.001) and lower resilience (P=0.024, P=0.034, and P=0.001). Not having children below 18 years correlated with higher perceived stress (P˂0.001). In linear regression analysis, age and gender emerged as significant predictors of both perceived stress and resilience. Female participants reported stress related to the risk of contracting COVID-19 (P=0.001), transmitting it to others (P=0.017), social isolation (P˂0.001), and having children at home due to school closures (P=0.000). A cohort of 239 participants repeated the survey within a two-month interval, revealed a statistically significant decrease in the CD-RISC scores (p < 0.001).HCPs in Jordan experienced moderate stress, high moral distress, and poor resilience during the COVID-19 pandemic. These factors may negatively affect the quality of oncology care. Urgent measures are necessary to support HCPs in coping with unforeseen circumstances in the future.